Community attitudes toward childbearing and abortion among HIV-positive women in Nigeria and Zambia (2013)
Although stigma towards HIV-positive women for both continuing and terminating a pregnancy has been documented, to date few studies have examined relative stigma towards one outcome versus the other. This study seeks to describe community attitudes towards each of two possible elective outcome of an HIV-positive woman’s pregnancy – induced abortion or birth – to determine which garners more stigma and document characteristics of community members associated with stigmatising attitudes towards each outcome. Data come from community-based interviews with reproductive-aged men and women, 2401 in Zambia and 2452 in Nigeria. Bivariate and multivariate analyses revealed that respondents from both countries overwhelmingly favoured continued childbearing for HIV-positive pregnant women, but support for induced abortion was slightly higher in scenarios in which anti-retroviral therapy (ART) was unavailable. Zambian respondents held more stigmatising attitudes towards abortion for HIV-positive women than did Nigerian respondents. Women held more stigmatising attitudes towards abortion for HIV positive women than men, particularly in Zambia. From a sexual and reproductive health and rights perspective, efforts to assist HIV-positive women in preventing unintended pregnancy and to support them in their pregnancy decisions when they do become pregnant should be encouraged in order to combat the social stigma documented in this paper.